The tribe and the power in the fatimidMghreb( showing figures of the aversion and the hostilityi.e, types of hostility) - chaki, abdelaziz (The Algerian Historical Journal, 2026)
The shiite Fatimid State is one of the countries that unified the Maghreb. The shiite layreadersrecognised that the maghreban people love the prophete family ; sot the yused this advantage to spread their thoughts and to establish their new State particularly so far from the Abassid one. They have been supported by bothe Kutama and Sanhaja tribe swithwhich they shared power and money. Although, the barbarian tribe – Zenata – refused the new situation ; as a result the Fatimid were not in good termswith Zenata tribe. They knew bad relationships full of hostility and lack of truce. Finally, Zenata tribe engaged in a long-term conflict with the Fatimid State and mobilised all rebels against this later.